Safety of uranium and plutonium mixed oxide fuel fabrication facilities : specific safety guide (International Atomic Energy Agency, 2010)
This safety guide supplements the safety requirements publication, Safety of fuel cycle facilities, and addresses all the stages in the life cycle of MOX fuel fabrication facilities (MFFFs), with emphasis placed on design and operation. It describes the actions, conditions and procedures for meeting safety requirements and deals specifically with the handling, processing and storage of plutonium oxide, depleted, natural or reprocessed uranium oxide, mixed oxide manufactured from the above to be used as a feed material to form MOX fuel rods and assemblies for export and subsequent use in water reactors and fast breeder reactors. The publication is intended to be of use to designers, operating organizations and regulators to ensure the safety of MOX fuel fabrication facilities.--Publisher's description.
"IAEA safety standards for protecting people and the environment."
"May 2010."
Keywords: Nuclear facilities -- Safety measures.; Mixed oxide fuels (Nuclear engineering) -- Safety measures.; elektronické knihy; electronic books